Would You Tell Me Which Way of Teaching Mathematics I Should Walk? - Dugois, Maria Eduarda Miranda; Tártaro, Tássia Ferreira [UNESP]; Da Silva, Michela Tuchapesk [UNESP] (FapUNIFESP (SciELO), 2023)
The Covid-19 pandemic destabilized school practices and, quickly, the State apparatus started a movement of (re)organization that imposed teaching and behavior models during the social isolation, This text discusses ideas regarding the norm, normalization,and the new normal in the face of the school processes that took place during the pandemic, seeking to tense new structures that institute old models, We problematize the concept of will to normality, rules, and regiments from the connections with the Philosophy of Difference, highlighting lines of force, affections and subjectivations in mathematics classes of the Pedagogical Residency Program of the third years of Integrated High School of a Federal Institute and a state school, Making connections withthe work Alice's Adventures in Wonderland, we built maps that mobilize other ideas in mathematics teaching, which enable the affirmation of the event as a potency of differentiation of the subject in a mathematics class.
Poderia Me Dizer que Caminho do Ensino da Matemática Devo Tomar?
Keywords: Cartography; Lines of Force; Philosophy of Difference; Remote Teaching; Will to Normality